Eksistensi Kantor Pertanahan Kota Palopo dalam Mengatasi Konflik Kepemilikan Tanah - Sumarni M.; Bahtiar, Bahtiar; Abdain, Abdain; Takdir, Takdir (Al-Mizan (e-Journal), 2024)
This study aims to examine the forms of land ownership conflicts in Palopo City. This research was conducted using qualitative method with the type of field research. Data collection in the form of primary data and secondary data through observation, interview and documentation techniques and literature studies through 4 stages, namely reduction (data is filtered/selected), connection (data is connected), interpretation (data is translated/explained) and conclusions (data is concluded). The results showed that: (1) land conflicts occurring in Palopo City are categorised into 4 categories, namely: land boundary conflicts, land ownership conflicts, inherited land conflicts, and conflicts between the government and the community/legal entity; (2) factors causing ownership conflicts, namely unclear land boundaries, incomplete land ownership documents, landowners do not manage their own land, land is not physically controlled, land is abandoned, undivided inherited land, dishonesty of heirs, multiple and overlapping certificate claims, and infrastructure development; (3) The Palopo City Land Office is an institution that has an important role in managing and regulating land aspects in its area by making efforts to minimise the occurrence of land conflicts.